Seasonal Variation in Corticosterone Receptor Binding in Brain, Hippocampus, and Gonads in House Sparrows (Passer domesticus). - Romero, L. Michael.; Lattin, Christine R. (Tufts University. Tisch Library., 2016)
Both baseline and stress-induced concentrations of corticosterone (CORT) vary seasonally in a predictable fashion in many wild birds. Hypotheses about why these patterns exist include the "behavior hypothesis," which predicts that animals will down-regulate stress-induced CORT when CORT-induced behaviors are too likely to cause reproductive failure; and the "preparative hypothesis," which posits that baseline and stress-induced CORT will both be high at times of year with a higher incidence of predictable stressors. We tested predictions made by the behavior and predictive hypotheses about the CORT sensitivity of tissues involved in breeding: whole brain, hippocampus, and gonads. We used radioligand binding assays to examine glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) binding in free-living House Sparrows (Passer domesticus) at several different life history stages. We found lowest GR binding in whole brain during breeding; this suggests relative insensitivity of brain tissue to CORT at this time of year, which is consistent with predictions made by the behavior hypothesis. We found highest GR binding in whole brain in the pre-egg-laying period, which is consistent with the preparative hypothesis, given that this life stage is associated with a predictable increase in the likelihood of stressful events such as threats to territory and nest sites. However, we found no seasonal changes in GR or MR binding in gonads or hippocampus. Our results suggest that down-regulation of brain GR could be one way birds limit the negative effects of CORT release on breeding behavior, but further studies are necessary to understand the anatomic specificity of these changes.